Fortress Attica : defense of the Athenian land frontier, 404-322 B.C. - Ober, Josiah. (Mnemosyne, Supplements, 1985)
This book analyzes the defense policy of Athens in the period after the Peloponnesian War. In order to counter new offensive strategies and to protect vital local sources of revenue, the Athenians instituted a system of territorial defense, based on massive frontier fortresses and a sophisticated signal network. Individual chapters treat Athens' postwar economic situations, the development of Greek military science, the rise of a defensive mentality among the Athenian citizens, theorectical literature on defense, and Athens' military establishment. A major section is devoted to detailed descriptions of the land routes into Attica and of all ancient fortresses, towers, and military highways in the frontier zones. Concluding chapters demonstrate how the defense system worked in practic.